“This new teaching method has no parallel in the history of education”: presence, tensions and versions of the Silabario Hispano Americano (1945) by Adrián Dufflocq Galdames - Pérez Navarro, Camila (Historia y Memoria de la Educación, 2024)
The Silabario Hispano Americano, written by Adrián Dufflocq, is one of the texts with the most significant presence in the Chilean collective memory. This syllabary has had almost a hundred editions since it first circulated in Chile in the mid-1940s. However, this syllabary has not yet been the subject of historiographical analysis despite its importance. Therefore, this article analyzes the Silabario Hispano Americano from a historical perspective. We delve into the context of its creation, the tensions generated by its publication, and the versions published by the Ministry of Public Education during the 1960s within the framework of implementing an adult literacy campaign. Methodologically, we studied different editions and versions of the Silabario, texts published in newspapers and magazines, as well as complementary documentary sources. Based on the evidence analyzed, we propose that the historical success of the Silabario can be explained, on the one hand, by the marketing strategy undertaken by its author; due to the simplicity of its methodology; and for the role it played in the literacy campaign carried out in the mid-1960s in Chile.